Building An Early Childhood Literacy Ecosystem Through Teacher and Parental Supervision in Meaningful Reading - Kamtini Kamtini; Salsabila Hasiana Tanjung; Dwi Maya Novitri (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2026)
ABSTRACT Basic literacy is an important foundation for the development of language, communication, and thinking skills in early childhood. However, literacy instillation efforts still face various challenges, such as low parental involvement, limited understanding of meaningful literacy among teachers and families, and a lack of synergy between the school and home environments. This community service activity aims to build an early childhood literacy ecosystem by mentoring teachers and parents in meaningful reading activities. The activity was carried out in Percut Sei Tuan District, Deli Serdang Regency, involving kindergarten teachers, parents, and school principals as participants. The methods used included counseling, training, interactive discussions, meaningful reading practices, and joint reflection. The material provided covered the concept of meaningful literacy, strategies for assisting children in reading, and the collaborative role of teachers and parents in building a culture of literacy from an early age. The results of the activity showed an increase in participants' understanding of the importance of meaningful literacy and the active role of families in supporting children's literacy development. Participants also demonstrated high enthusiasm through discussions, sharing experiences, and a commitment to implementing literacy practices at home and at school. This activity contributed to strengthening school-family partnerships, thus establishing a literacy ecosystem that supports optimal child development. Keywords: Meaningful Literacy, Early Childhood, Literacy Ecosystem.